Clinical efficacy of a topical lactic acid bacterial microbiome in chronic rhinosinusitis: A randomized controlled trial. Issue 6 (8th November 2017) - Mårtensson, Anders; Abolhalaj, Milad; Lindstedt, Malin; Mårtensson, Anette; Olofsson, Tobias C.; Vásquez, Alejandra; Greiff, Lennart; Cervin, Anders
Abstract : Objective: A locally disturbed commensal microbiome might be an etiological factor in chronic rhinosinusitis (CRS) in general and in CRS without nasal polyps (CRSsNP) in particular. Lactic acid bacteria (LAB) have been suggested to restore commensal microbiomes. A honeybee LAB microbiome consisting of various lactobacilli and bifidobacteria have been found potent against CRS pathogens in vitro. Recently, we examined effects of single nasal administrations of this microbiome in healthy subjects and found it inert. In this study, we examined effects of repeated such administrations in patients with CRSsNP. Study Design: The study was of a randomized, double‐blinded, crossover, and sham‐controlled design. Methods: Twenty patients received 2 weeks' treatment administered using a nasal spray‐device. The subjects were monitored with regard to symptoms (SNOT‐22 questionnaire, i.e., the primary efficacy variable), changes to their microbiome, and inflammatory products (IL‐6, IL‐8, TNF‐, IL‐8, a, and MPO) in nasal lavage fluids. Results: Neither symptom scores, microbiological explorations, nor levels of inflammatory products in nasal lavage fluids were affected by LAB (c.f. sham). Conclusion: Two weeks' nasal administration of a honeybee LAB microbiome to patients with CRSsNP is well tolerated but affects neither symptom severity nor the microbiological flora/local inflammatory activity. Level of Evidence: 1b